2023
DOI: 10.1111/fare.12815
|View full text |Cite
|
Sign up to set email alerts
|

Young adults' perceptions of technology use with extended family

Abstract: Objective The current study explores young adults' perceptions of the use and impact of technology on their relationships with extended family. Background Young adults are avid technology users and communicate frequently with parents and siblings using a variety of online tools. There is limited research examining young adults' use of technology to communicate with extended family members, despite studies suggesting that these relationships serve a unique and valuable role in their lives. Method Qualitative da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Contrary to a form of "selective mutism" or estrangement between children and parents, SMP usage may, in fact, enhance or at least maintain actual communication levels between them. This finding is consistent with numerous international studies that have highlighted the role of SMPs in fostering and sustaining parent-child connections (Ball et al, 2013;Child et al, 2015;Hessel and LeBouef, 2023) because they enable parallel communication with direct communication and integrate with it.…”
Section: Outcomes and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Contrary to a form of "selective mutism" or estrangement between children and parents, SMP usage may, in fact, enhance or at least maintain actual communication levels between them. This finding is consistent with numerous international studies that have highlighted the role of SMPs in fostering and sustaining parent-child connections (Ball et al, 2013;Child et al, 2015;Hessel and LeBouef, 2023) because they enable parallel communication with direct communication and integrate with it.…”
Section: Outcomes and Discussionsupporting
confidence: 91%
“…Students' use of SMPs and their gratifications are influenced by their social and cultural traits, as determined by the second purpose of the study, which was to assess the influence of family on the students' use of SMPs (Al Omoush et al, 2012). The research found that students are affected by SMPs in terms of their relationships, values, and standards of traditional family culture, which plays a crucial role in molding the uses and defining the gratifications (Karimi et al, 2014;Leijse et al, 2023;Saputri and Yumarni, 2023;Hessel and LeBouef, 2023). In the same context, it is posited that students' motivations for using Facebook exhibit variation based on their cultural backgrounds.…”
Section: Outcomes and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their article, Hessel and LeBouef (2023) explore young adults' perceptions of technology use with extended family members in the United States. The authors show that ICT increases the intensity of communication exchanges with extended family members, but not necessarily their depth and intimacy.…”
Section: This Special Issuementioning
confidence: 99%